Pengembangan Pop Up Book Bahasa Indonesia Berbasis Budaya Slempitan - Nanang Khoirul Umam; Afakhrul Masub Bakhtiar; Hardian Iskandar (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2019)
Innovation in education world is a nuance that must always be improved, considering that time goes with the changing of era. So in the field of education there has to be a special touch in the form of innovation which is able to become an educational identity as a space for freedom from backwardness. Education is now designed to return to the local wisdom of each region so that it can produce scholars with extensive knowledge and cultured character. Slempit Village is one of the villages in Gresik Regency with unique local culture and now has to get special attention for some of them are starting to get abandoned as modern access which is marked by the construction of the Gresik-Mojokerto toll road. Various elements of society have the same responsibility for cultural preservation and especially in the world of education which focuses directly on the inculcation of values towards the nation's next generations. Based on this, the researchers conducted the Development of Indonesian Language Pop Up Book Based on Slempitan Culture. The development process is carried out with a research method of development which then gives birth to a pop-up book which is effective and relevant to be applied in the learning process, especially at SDN I Slempit regarding local culture of Slempit. The development model is done by adapting instructional development model which, according to Sadiman, 1996 (et al) consists of seven systematic stages. This study used validation instruments from the data analysis. The validation of Slempitan Culture-Based Indonesian Pop-Up Book consists of presentation / material validator as well as graphic validator. The results of the validation of the presentation obtained a score of 90% in the very feasible category. While the score obtained from the results of the graphic is 90.9% in the excellent category.